Treatment and Outcome Analysis of 205 Patients with Multidrug-resistant Tuberculosis - Chan, Edward D; Laurel, Valerie; Strand, Matthew J; Chan, Julanie F; Huynh, Mai-Lan N; Goble, Marian; Iseman, Michael D (American journal of respiratory and critical care medicine, 2004)
Multidrug-resistant tuberculosis, a disease caused by Mycobacterium tuberculosis strains that are resistant at least to rifampin and isoniazid, entails extended treatment, expensive and toxic regimens, and higher rates of treatment failure and death. We retrospectively analyzed the outcomes in 205 patients treated at our center for multidrug-resistant tuberculosis, with strains resistant to a median of six drugs, and compared the results with those of our previous series. Logistic regression and survival analysis were used to evaluate short- and long-term outcomes, respectively. Initial favorable response, defined as at least three consecutive negative sputum cultures over a period of at least 3 months, was 85% compared with 65% in the prior cohort. The current cohort had greater long-term success rates, 75% versus 56%, and lower tuberculosis death rates, 12% versus 22%, than the earlier one. Surgical resection and fluoroquinolone therapy were associated with improved microbiological and clinical outcomes in the 205 patients studied after adjusting for other variables. The improvement was statistically significant for surgery and among older patients for fluoroquinolone therapy.